Understanding User Attraction To E-Book For Digital Learning And Informations Access - Nurranto, Heri; Suhud, Usep; Rizan, Mohamad (Siber International Journal of Digital Business (SIJDB), 2025)
This study aims to identify the key factors driving e-book adoption in supporting learning and digital information access. Using a quantitative approach and questionnaire-based survey, the research explores the role of accessibility, cost and time efficiency, reference completeness, digital feature innovation, and environmental sustainability as central elements in e-book attractiveness. The findings indicate that ease of access and interactive features are the primary drivers of e-book adoption, especially among students and academics. Additionally, psychological factors such as perceived usefulness and ease of use significantly influence user preferences. This study provides valuable insights for digital platform developers and publishers in designing more relevant, innovative, and user-oriented e-books in the era of digital transformation.